History of the West Asian Championship football (Journal of the College of Basic Education, 2022)
This research deals with the study of (the history of the West Asian Football Championship) since the launch of its first edition in the year (2000), which was held in Jordan at the time, until the eighth edition of it, which was held in Qatar at the end of the year (2013) and the beginning of the year (2014), and the research includes a description An analysis of the competitions of each of these tournaments in terms of the results and statistics of the tournament in general and the participating teams in particular, as well as the tournament system, the method of drawing lots and the mechanism for selecting the host countries for each tournament.